PKM Utilization of Learning Resources in Improving the Quality of the Learning Process in the Mutiara Bahari Play Group - Irma Yuliantina; Nuris Azizah; Indro Wiyarno; Ria Andriani; Venty Indah; Siti Maesyaroh; Leny; Mulyanti; Susy Anggriani; Mardiananingsih (PT FORMOSA CENDEKIA GLOBAL, 2023)
Community Service Activities (PKM) are carried out in one unit of the Mutiara Bahari Playgroup because it has a large number of students with limited learning resources and teacher competence. PKM is conducted from October to November by going through several stages including: initial identification on October 22 2022, debriefing on learning concepts on November 5 2022, workshop on implementing the use of learning resources in improving the quality of the learning process on November 11 2022, testing field trials from November 14 to 28, program evaluation in the first week of December. The change felt by the teacher is that for sufficient learning resources from the natural surroundings, there is no need to use materials or media from the manufacturer, and the most enjoyable thing is that children usually ask to go home during the learning process after activities are carried out using learning resources from the surrounding environment in an attractive arrangement. Children are more enthusiastic to come to school and do various creativity according to the imagination of each child.